2019
DOI: 10.3390/cancers11030371
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Radiation Oncologists in The Management of Older Cancer Patients: Consensus of The International Geriatric Radiotherapy Group

Abstract: The management of older cancer patients remains difficult because of data paucity. Radiation oncologists need to identify potential issues which could affect treatment of those patients. A workshop was organized in Barcelona among international radiation oncologists with special interest in the management of older cancer patients on April 22, 2018. The following consensus was reached: 1. Older cancer patients often faced unconscious discriminating bias from cancer specialists and institutions because of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…The selection was limited to mastectomy without radiotherapy to avoid treatment interaction. Age was limited to >50 and <65 years to reduce the influence of age-related co-morbidity and to reduce the variability with age in the receipt of treatments [6-7]. After cleaning the data of discrepancies, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The selection was limited to mastectomy without radiotherapy to avoid treatment interaction. Age was limited to >50 and <65 years to reduce the influence of age-related co-morbidity and to reduce the variability with age in the receipt of treatments [6-7]. After cleaning the data of discrepancies, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the combination of immunotherapy and radiotherapy may be an attractive concept to improve survival and quality of life for older cancer patients during this uncertain time. As an international organization devoted to the care of older cancer patients, women, and minority, the International Geriatric Radiotherapy Group ( http://www.igrg.org ) [ 13 ] would like to take the initiative to recommend an innovative treatment to that population who is often discriminated. This review examines the preliminary data reporting the possible beneficial effect of immunotherapy and radiotherapy and proposes a new paradigm for the management of older cancer patients during the COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, due to a decline of physical and physiological functions, many older patients cannot tolerate ICI combination immunotherapy, chemotherapy, radiotherapy, or targeted therapy. Some reports have also demonstrated that ICI combination immunotherapy, chemotherapy, radiotherapy, and/or targeted therapy is less effective in older people than in younger people (5,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%